2010
DOI: 10.1111/j.1365-2672.2009.04406.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the wine fermentation performance of Saccharomyces paradoxus under different nitrogen concentrations and glucose/fructose ratios

Abstract: Aims: The main goal of the present study is to determine the effects of different nitrogen concentrations and glucose ⁄ fructose ratios on the fermentation performance of Saccharomyces paradoxus, a nonconventional species used for winemaking. Methods and Results: Ethanol yield, residual sugar concentration, as well as glycerol and acetic acid production were determined for diverse wine fermentations conducted by S. paradoxus. Experiments were also carried out with a commercial Saccharomyces cerevisiae wine str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
(67 reference statements)
4
23
0
Order By: Relevance
“…Within the tolerance range of osmotic stress, more glycerol were produced with the increasing of sugar concentration ( Arroyo-López et al 2010;Erasmus et al 2004;Jiménez-Martí et al 2011;Orlic et al 2010;Piddocke et al 2009;Radler and Schütz 1982). As illustrated in Fig.…”
Section: Sugar Concentration Is Positively Related To Glycerol Yieldmentioning
confidence: 92%
See 3 more Smart Citations
“…Within the tolerance range of osmotic stress, more glycerol were produced with the increasing of sugar concentration ( Arroyo-López et al 2010;Erasmus et al 2004;Jiménez-Martí et al 2011;Orlic et al 2010;Piddocke et al 2009;Radler and Schütz 1982). As illustrated in Fig.…”
Section: Sugar Concentration Is Positively Related To Glycerol Yieldmentioning
confidence: 92%
“…Higher proportion of fermentable sugar enhanced glycerol formation (Myers et al 1997). Glycerol was higher in the fermentation of glucose rich medium than in medium with maltose addition (Orlic et al 2010;Piddocke et al 2009). The reason could be that more DHAP and NADH were generated in high monosaccharide condition.…”
Section: Sugar Concentration Is Positively Related To Glycerol Yieldmentioning
confidence: 96%
See 2 more Smart Citations
“…This study and others have demonstrated that free cells of S.cerevisiae maintain about 10% viability for 2 weeks whilst less than 1% of entrapped cells remain viable after one month (Ghose and Bandyopadhyay, 1982;Laopaiboon et al, 2009;Yamada et al, 2009;Basso et al, 2010;Orlic et al, 2010;Turhan et al, 2010;Yu et al, 2010;Ghorbani et al, 2011).…”
Section: Discussionmentioning
confidence: 62%